2005
DOI: 10.1103/physreve.72.021406
|View full text |Cite
|
Sign up to set email alerts
|

Structure, normal mode spectra, and mixing of a binary system of charged particles confined in a parabolic trap

Abstract: We study the mixing of two different kinds of particles, having different charge and/or mass, interacting through a pure Coulomb potential, and confined in a parabolic trap. The structure of the cluster and its normal mode spectrum are analyzed as a function of the ratio of the charges (mass ratio) of the two types of particles. We show that particles are not always arranged in a shell structure. Mixing of the particles goes hand in hand with a large number of metastable states. The normal modes of the system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 19 publications
5
33
0
Order By: Relevance
“…The annealing time is 6 × 10 4 ω −1 0 , and the integration time step is 0.003ω −1 0 . We have checked the accuracy of our simulations by comparing our results to the stable-state configurations of single-or two-species clusters obtained from Monte Carlo (MC) or MD simulations [20,21,32,34]. We found very good agreement between our results and those obtained from these MC and MD simulations.…”
Section: Model System and Numerical Approachsupporting
confidence: 51%
See 1 more Smart Citation
“…The annealing time is 6 × 10 4 ω −1 0 , and the integration time step is 0.003ω −1 0 . We have checked the accuracy of our simulations by comparing our results to the stable-state configurations of single-or two-species clusters obtained from Monte Carlo (MC) or MD simulations [20,21,32,34]. We found very good agreement between our results and those obtained from these MC and MD simulations.…”
Section: Model System and Numerical Approachsupporting
confidence: 51%
“…The studies have found that in an isotropic (circular) confinement potential, the particles of different species segregate into different shells, with the particles of the largest (smallest) mass-to-charge ratio tending to populate near to (far away from) the system center [35]. The different particles also become mixed together if they have the same mass-to-charge ratio, although their individual masses and charges [34,35] are different. The investigation performed so far on 2D multi-species systems has been restricted to confinement in an isotropic potential.…”
Section: Introductionmentioning
confidence: 99%
“…the curious ground state configuration found in a 3D finite size binary Coulomb cluster 5 , where a mixed arrangement of the two types of particles was observed in the core, while the edge of the system was characterized by shell structures of separated species. Similarly, in 2D systems we can cite a reentrant melting phenomenon in a 2D circular confined cluster of repulsive dipoles 6,7 , and interesting asymmetrical ground state configurations observed in symmetrically confined Coulomb clusters 8,9 .…”
Section: Introductionmentioning
confidence: 63%
“…We only considered equal mass particles. If masses are taken different the two types of particles will feel a different confinement potential which will result in a quantitative modification of the phase diagram 8 .…”
Section: Ground State Crystal Structuresmentioning
confidence: 99%
“…Many numerical studies have been performed to investigate the crystallization and melting in the above systems by simulating a model system of charged classical pointlike particles, i.e. a Wigner-type crystal [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%